Comparing Self-Reported Infant Safe Sleep From Community- and Health Care–Based Settings. (July 2015) - Keene Woods, Nikki; Ahlers-Schmidt, Carolyn R.; Wipperman, Jennifer; Williams, Tracy
Objective: To compare self-reported safe sleep data from a community social service agency and primary care centers.Design, Settings, and Participants: Cross-sectional Pregnancy Risk Assessment Monitoring System (PRAMS)–based survey data from a community social service agency and survey data from primary care centers were compared using descriptive statistics. There were 166 community survey respondents, average age of 25 years (SD = 5.4 years), and 79 primary care center respondents, average age of 24 years (SD = 5.4 years). Two binary logistic regressions were performed to examine the association between demographic differences and safe sleep position/bed sharing.Results: Safe sleep position responses did not differ significantly between the community-based (n = 126, 85%) and primary care center–based (n = 62, 79%) samples, χ 2 (1) = 0.79, P = .372. Reported bed sharing was significantly higher in the community sample (n = 54, 36%) than the health care center sample (n = 4, 5%), Fisher's exact test, P < .001. Black race was determined to be significantly associated with increased unsafe sleep positioning (OR = 2.86, P = .022). The community center cohort was the only significant predictor of bed sharing (OR = 25.40, P = .002).Conclusion: Differences in reported safe sleep environments may be due to knowledge variances of safe sleep guidelines, or clinic-based respondents may have been more likely to provide socially desirable responses. The comparison data further highlight the need for continued targeted effort to improve safe sleep behaviors to improve infant health outcomes.